2013
DOI: 10.1073/pnas.1306723110
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt2-dependent methylomes lack defined DNA methylation patterns

Abstract: Several organisms have retained methyltransferase 2 (Dnmt2) as their only candidate DNA methyltransferase gene. However, information about Dnmt2-dependent methylation patterns has been limited to a few isolated loci and the results have been discussed controversially. In addition, recent studies have shown that Dnmt2 functions as a tRNA methyltransferase, which raised the possibility that Dnmt2-only genomes might be unmethylated. We have now used whole-genome bisulfite sequencing to analyze the methylomes of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
216
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(230 citation statements)
references
References 43 publications
12
216
0
2
Order By: Relevance
“…The relative rarity of methylation in Drosophila, even at stage 5 where it has been shown to be most abundant (Lyko et al 2000a), has made it a subject of controversy. Some have recently suggested that it may be absent, or its presence is spurious and a reflection of nonspecific activity by MT2 (Marhold et al 2004;Schaefer and Lyko 2010a;Raddatz et al 2013); the near-normal phenotype of flies lacking functional MT2 has supported this point of view (Kunert et al 2003;Phalke et al 2009;Schaefer and Lyko 2010b). Although we find that methylation can be present on a substantial proportion of alleles within methylated regions, methylation is virtually never present on more than half of the alleles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The relative rarity of methylation in Drosophila, even at stage 5 where it has been shown to be most abundant (Lyko et al 2000a), has made it a subject of controversy. Some have recently suggested that it may be absent, or its presence is spurious and a reflection of nonspecific activity by MT2 (Marhold et al 2004;Schaefer and Lyko 2010a;Raddatz et al 2013); the near-normal phenotype of flies lacking functional MT2 has supported this point of view (Kunert et al 2003;Phalke et al 2009;Schaefer and Lyko 2010b). Although we find that methylation can be present on a substantial proportion of alleles within methylated regions, methylation is virtually never present on more than half of the alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of Mt2 does not visibly alter embryonic development (Kunert et al 2003), although it can suppress position-effect variegation (Phalke et al 2009). No clear pattern of genomic cytosine methylation has been established by any study, and genomewide bisulfite sequencing studies of wild type Drosophila embryos at an average depth of 5.6-fold (Zemach et al 2010) and 32-fold (Raddatz et al 2013) did not report methylated cytosines. The finding that MT2 can methylate tRNAs has led to speculation that its primary function in Drosophila is RNA methylation (Goll et al 2006;Schaefer et al 2010;Durdevic et al 2013), and that genomic cytosine methylation is random and spurious (Schaefer and Lyko 2010b).…”
mentioning
confidence: 86%
See 3 more Smart Citations